Strategic behavior across gender: a comparison of female and male expert chess players - Christer Gerdes; Patrik Gränsmark (Institute for the Study of Labor (IZA), 2010)
This paper aims to measure differences in risk behavior among expert chess players. The study employs a panel data set on international chess with 1.4 million games recorded over a period of 11 years. The structure of the data set allows us to use individual fixed-effect estimations to control for aspects such as innate ability as well as other characteristics of the players. Most notably, the data contains an objective measure of individual playing strength, the so-called Elo rating. In line with previous research, we find that women are more risk-averse than men. A novel finding is that males choose more aggressive strategies when playing against female opponents even though such strategies reduce their winning probability.
Keywords: J16; J70; J71; D03; 330; Risk aversion; competitiveness; gender; culture; mixed-sex competition